AVENCCA - Ambiente Virtual para Encontros de Sentido, Construções Conceituais e Aprendizagem - Martins, Ademir da Rosa; Lapolli, André; Paiva, Daniela Peño; Axt, Margarete; Guimarães, Lucas Nunes (RENOTE, 2003)
Não disponível